The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.15939
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic signature distinguishes pediatric and adult rhabdoid tumors from other SMARCB1-deficient cancers

Abstract: Extra-cranial rhabdoid tumors (RT) are highly aggressive malignancies of infancy, characterized by undifferentiated histological features and loss of SMARCB1 expression. The diagnosis is all the more challenging that other poorly differentiated cancers lose SMARCB1 expression, such as epithelioid sarcomas (ES), renal medullary carcinomas (RMC) or undifferentiated chordomas (UC). Moreover, late cases occurring in adults are now increasingly reported, raising the question of differential diagnoses and emphasizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…An embryonic gene expression signature distinguishes RT from other cancers that are SMARCB1-deficient (Richer et al 2017). Consistent with SWI/SNF's role as a member of the TrxG, dysregulation of Hox genes is frequently observed in RTs (Chun et al 2016;Torchia et al 2016;Richer et al 2017;Pinto et al 2018). Although more research is required to determine the significance of specific transcriptional perturbations in RT, the retention of an embryonic signature is likely a key aspect in the development of these tumors.…”
Section: Smarcb1 In Rhabdoid Tumorsmentioning
confidence: 93%
See 2 more Smart Citations
“…An embryonic gene expression signature distinguishes RT from other cancers that are SMARCB1-deficient (Richer et al 2017). Consistent with SWI/SNF's role as a member of the TrxG, dysregulation of Hox genes is frequently observed in RTs (Chun et al 2016;Torchia et al 2016;Richer et al 2017;Pinto et al 2018). Although more research is required to determine the significance of specific transcriptional perturbations in RT, the retention of an embryonic signature is likely a key aspect in the development of these tumors.…”
Section: Smarcb1 In Rhabdoid Tumorsmentioning
confidence: 93%
“…While several studies have addressed the alterations in gene expression in RT; interpretations have been complicated by the substantial heterogeneity among tumors (Chun et al 2016;Torchia et al 2016;Richer et al 2017;Pinto et al 2018). An embryonic gene expression signature distinguishes RT from other cancers that are SMARCB1-deficient (Richer et al 2017).…”
Section: Smarcb1 In Rhabdoid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if the RMC cell lines clustered separately among other SMARCB1-deficient cancers, we performed gene expression analysis of our RMC models and compared them to publicly available datasets of MRT cell lines, patients with RMC, MRT or ATRT or synovial sarcoma (a cancer driven by the fusion oncoprotein SSX-S18 which displaces SMARCB1; Methods ) (Barretina et al, 2012; Calderaro et al, 2016; Han et al, 2016; Johann et al, 2016; Richer et al, 2017). Using tSNE, we found that the RMC cell lines closely mapped to a French cohort of RMC, MRT and ATRT patients ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed Affymetrix Human Genome U133 Plus 2.0 on our RMC cell lines. We then combined the following GEO datasets using a GenePattern module with robust multi-array (RMA) normalization GSE64019, GSE70421, GSE70678, GSE36133, GSE94321 (Barretina et al, 2012; Calderaro et al, 2016; Johann et al, 2016; Richer et al, 2017; Wang et al, 2016). We utilized COMBAT and then tSNE to account for batch effects and to identify clusters of similarity (Chen et al, 2011; Johnson et al, 2007; Maaten, 2014).…”
Section: Methodsmentioning
confidence: 99%